SOME PROBLEMS IN ARRANGING IN PATIENT AID FOR TEENAGERS - V.K. Yuriev; A.V. Golovanov; A.D. Rubin (Вопросы современной педиатрии, 2006)
A special medical and social survey was conducted to compare the quality of medical aid for teenagers at children's hospitals. The survey findings indicate that treatment of teenagers at adult inapatient hospitals and children's hospitals has both advantages and disadvantages. Thus, teenagers' treatment at children's hospitals provides for a better consistency with the primary stage of the health care system — such hospitals offer better conditions and wider possibilities for consulting. The adult inapatient departments the laboratory and instrumental examinations as well as consulting of experts are of lower quality, preahospital stage studies are often duplicated. Therefore, basing upon the findings the article recommends the health care authorities target at local conditions and opportunities in arranging inapatient aid for teenagers giving preference to treatment at children's inapatient hospitals and departments.Key words: in patient aid, teenagers.